Analyzing cultural disparities and gender in science literacy and numeracy among senior high school students in Sundaland, Indonesia - Yulianto, Dwi; Situmeang, Muhamad Sukri; Junaedi, Yusup; Anwar, Syahrul; Umami, Moh Rizal (Indonesian Journal of Science and Mathematics Education, 2026)
Gender and cultural disparities remain pressing challenges in STEM education across Indonesia’s multi-ethnic regions, particularly in Sundaland, where variations in school accreditation, infrastructure readiness, and mother-tongue use stratify learning opportunities. This study examines differences in scientific literacy and numeracy, focusing on the roles of ethnicity, Socioeconomic Status (SES), and mother-tongue use, while also exploring their interactions with gender and school-level conditions. A quantitative survey design using Hierarchical Linear Modeling (HLM) was applied to capture both student- and school-level variations. Data were collected through literacy tests, questionnaires, and interviews from a stratified sample categorized by accreditation, gender, and SES. The results show that Javanese students achieved the highest scores, while Balinese students obtained the lowest in both competencies, largely reflecting differences in infrastructure and technological support. Male students outperformed in numeracy, whereas females excelled in scientific literacy. Mother-tongue use enhanced conceptual understanding, particularly among Batak and Minangkabau students with strong learning traditions. The implications of this research emphasize the need for inclusive and culturally responsive STEM education policies, which can be achieved by strengthening multilingual education, adopting ethnomathematics approaches, and equalizing school quality to reduce the gap in science literacy and numeracy.